THE USE OF STAD TECHNIQUE TO IMPROVE THE STUDENTS’ READING ACHIEVEMENT AT CLASS XI IA1 OF SMAN 7 KENDARI - Citra Prasiska Puspita Tohamba (Journal of English Education, 2017)
The objective of the study is to investigate the improvement of students’ reading achievement by applying one of cooperative learning techniques namely STAD technique at class XI IA 1 of SMAN 7 Kendari. The target of this study is 70% of total students at class XI IA 1 who are expected to get 65 (based on standard of minimum score of the school). The design of this study is a Classroom Action Research (CAR) that involves four stages, namely: 1) planning, 2) action, 3) observation, 4) reflection. This study is conducted in two cycles because the target has been achieved successfully in which each cycle consists of three meetings. The research data are collected by 1) test, 2) observation sheets, and 3) field note. Based on the data in pre-observation, there were problems in students reading achievement 1) students could not find out specific information of narrative text, 2) they found difficulty to identify main idea of the text, 3) they could not determine the generic structure of narrative text correctly, (4) they did not know the meaning of the text well because they sometimes found unfamiliar words. The result of this study shows that STAD technique as cooperative learning model can improve the students’ reading achievement at class XI IA 1 of SMA Negeri 7 Kendari in academic year 2010/2011. It is reflected from the improvement of students’ score of reading test in every cycle, in which, at the first cycle, the total number of students who can get the score of ≥ 65 is 18 students or 56.3% of 32 students, with the mean score is 62.2. Moreover, after conducting the first cycle, two problems that identified in the preliminary research can be treated well in which students can find detail information from reading text and they can determine the generic structure of the narrative text. Nevertheless, the target of students’ reading achievement has not achieved yet and there are some problems that have not been treated well. Thus, this study is continued to the second cycle, where in the second cycle, the weaknesses and constraints in the first cycle are solved effectively. It can be indicated by the students’ reading improvement, in which students can get main idea of the reading text and they know how to guess the unfamiliar word. Besides, students help each other, interact, discuss with the teacher and their classmates, contribute scores for teams, give respect to others, and become independent and good students. Therefore, in the end of the second cycle, the target achievement of this study is achieved, where there are 84.4 % or 27 students of 32 students at class XI IA 1 get the score ≥ 65.  In brief, STAD technique is an effective technique that can improve students’ reading achievement at class XI IA 1 of SMA Negeri 7 Kendari.